2002
DOI: 10.1063/1.1513187
|View full text |Cite
|
Sign up to set email alerts
|

Electrical response of amorphous silicon thin-film transistors under mechanical strain

Abstract: We evaluated amorphous silicon thin-film transistors (TFTs) fabricated on polyimide foil under uniaxial compressive or tensile strain. The strain was induced by bending or stretching. The on- current and hence the electron linear mobility µ depend on strain as µ = µ0(1 + 26E), where tensile strain has a positive sign and the strain is parallel to the TFT source-drain current path. Upon the application of compressive or tensile strain the mobility changes "instantly" and under compression then remains constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(106 citation statements)
references
References 17 publications
1
105
0
Order By: Relevance
“…The change in the on-current was 3.9%, and the change in the mobility was 1.6% with bending and the on/off ratio remained more than 10 5 . The ultra-thin film substrates help reduce the applied strain in the TFT devices, whereby the calculated strain was B0.5% or less, even when the devices were bent to a radius of 140 mm 38,39 . As several research groups have already reported, such a small degree of strain does not significantly change the electrical performance of organic TFT devices 39,40 .…”
Section: Articlementioning
confidence: 99%
“…The change in the on-current was 3.9%, and the change in the mobility was 1.6% with bending and the on/off ratio remained more than 10 5 . The ultra-thin film substrates help reduce the applied strain in the TFT devices, whereby the calculated strain was B0.5% or less, even when the devices were bent to a radius of 140 mm 38,39 . As several research groups have already reported, such a small degree of strain does not significantly change the electrical performance of organic TFT devices 39,40 .…”
Section: Articlementioning
confidence: 99%
“…109 Further enhancement in the minimum of radii of curvature (R [1.6, 70] mm) is achieved in a-Si:H thin-film transistors (TFTs) fabricated on 25 lm thick Kapton foil. 169 …”
Section: B Stress Effects In Mosfetsmentioning
confidence: 99%
“…[14]- [16] Mechanical stability of organic electronic devices has been thoroughly explored in the last decade, in particular for Organic Field-Effect Transistors (OFETs), and it was found that, in this kind of structure, the mechanical sensitivity is mainly related to the morphological characteristics of the organic semiconductor film. [17]- [21] Indeed, by applying a mechanical deformation inducing an elongation of a layer from L to L+∆L ,a surface strain ε = ΔL/L, is induced. In the case of thin-film devices, where the overall thickness of the device is negligible with respect to the one of the substrate (t sub ), the thin-film strain (ε) obtained by bending the substrate with a certain bending radius R is given by the relationship…”
Section: Introductionmentioning
confidence: 99%